What is a genus—interpreting structural diversity among species of urothripine Phlaeothripinae (Thysanoptera) - Mound, Laurence A.; Lima, Élison Fabrício B.; O’donnell, Cheryle A. (Zootaxa, 2023)
Variation within and between species is discussed in several obvious character states, including the number of visible antennal segments, prolongation of the anterior margin of the head, metaepimeral setae, and anal setae. As a result, Bebelothrips and Conocephalothrips are considered new synonyms of Amphibolothrips, and Baenothrips a new synonym of Stephanothrips. The revised generic classification suggests that urothripines are largely absent from the Neotropics, with four recorded species all likely to be introductions from the Old World.